URBAN CHANGES AND CITIZENS’ ENGAGEMENT BY USING DIGITAL MEDIA - NECHITA, F (Universitatea Transilvania Brasov, 2019)
New media and digital communication tools give an authentic voice to citizens, allowing them not only to be better informed, but also to be initiators of social change. Relatively new concepts related to digital communication tools that are extensively used in business and brand communication (co-creation, digital storytelling, virtual worlds or gamification) have to be considered from the perspective of engaging citizens in urban planning, design or urban regeneration projects Three international case studies are briefly described as examples of good practice for a creative and innovative way of using digital media tools for engaging citizens with theirs cities.
Keywords: participation; engagement; digital communication